Driving change: Factors influencing smart/automated parking system adoption in Thailand - Tankongchamruskul, Wichai; Chaveesuk, Singha; Chaiyasoonthorn, Wornchanok (Edelweiss Applied Science and Technology, 2026)
This study aims to explore the determinants of automated parking systems (APS)/smart parking systems (SPS) adoption among small and medium-sized enterprises (SMEs) in Bangkok. The study examines the influence of technology trust (TT), environmental consciousness (EC), and perceived risk (PR) on commuter behavioral intention (BI). The model also addresses the critical moderating role of parking space availability (PSA). Structural Equation Modeling (SEM) was used on 469 responses collected from SME commuter employees. The findings identified facilitating conditions (FC) (β = 0.473) and TT (β = 0.359) as the strongest direct APS/SPS adoption drivers, followed by EC (β = 0.186) at a significant practitioner level, while, unexpectedly, PR’s negative influence on APS/SPS adoption intention was not significant. Finally, the moderating test results indicated a significant strengthening moderating effect of parking space availability (PSA) on the negative influence of price value (PV) on PR, and an unexpected weakening moderating effect of PSA on the positive influence of FC on TT at a high customer demand level, to an insignificant extent. The results provide a refined theoretical model of technology adoption in highly demanding urban contexts, along with actionable recommendations for policymakers, providers, and SMEs in the APS/SPS sector, to inform the development of sustainable urban mobility solutions.